1986
DOI: 10.1007/bf02926830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal ions on aflatoxin production byAspergillus parasiticus

Abstract: The effect of iron, copper, cobalt, cadmium, zinc, molybdenum, magnesium and manganese salts was studied on aflatoxin production in relation to mycelial mass. Iron, copper and cadmium salts decreased the aflatoxin production to different levels but a mixed trend was observed depending on salt concentration, with molybdenum, magnesium and manganese. Cobalt and zinc salts stimulated aflatoxin production at all concentrations studied. The maximum increase in aflatoxin production, 655% and 519% was observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Maggon et al (1973) observed inhibition of aflatoxin synthesis at low levels of manganese in the medium whereas higher levels resulted in enhanced aflatoxin formation but at some intermediate concentrations of manganese, there was no effect on aflatoxin biosynthesis. A mixed trend was also reported by Tiwari et al (1986): stimulation with 0.2, 0.5 and 1.2 mmol I-' and inhibition with 0.7 mmol 1of manganous chloride. However, when manganous sulphate was used aflatoxin production decreased despite the concentration.…”
Section: The Role Of T R a C E M E T A L Ssupporting
confidence: 52%
See 3 more Smart Citations
“…Maggon et al (1973) observed inhibition of aflatoxin synthesis at low levels of manganese in the medium whereas higher levels resulted in enhanced aflatoxin formation but at some intermediate concentrations of manganese, there was no effect on aflatoxin biosynthesis. A mixed trend was also reported by Tiwari et al (1986): stimulation with 0.2, 0.5 and 1.2 mmol I-' and inhibition with 0.7 mmol 1of manganous chloride. However, when manganous sulphate was used aflatoxin production decreased despite the concentration.…”
Section: The Role Of T R a C E M E T A L Ssupporting
confidence: 52%
“…1967). In contrast to Davis et al (1967) andMaggon et al (1973), Tiwari et al (1986) reported inhibition of aflatoxin production by iron salts. Maggon et al (1973) pointed out that the protein binding activity of different metals is, in decreasing order, Cu, Zn, Co, Fe, Mn and Ca which corresponded roughly with the ability of the trace metal ions to stimulate aflatoxin production observed in their study.…”
Section: The Role Of T R a C E M E T A L Smentioning
confidence: 79%
See 2 more Smart Citations
“…1984). In a completely zinc-limited medium, cadmium ions will stimulate growth and versicolorin production in a mutant strain of A. parasiticus (Failla & Niehaus 1986) although Tiwari et al (1986a) reported that CdZ+ repressed aflatoxin production. It is not unusual to find apparently conflicting reports in the literature about secondary metabolite studies and they reflect the need for very careful descriptions of experimental method-A number of filamentous fungi can produce ethylene and it seems that A .…”
Section: Mossmentioning
confidence: 99%